2013
DOI: 10.1037/a0028093
|View full text |Cite
|
Sign up to set email alerts
|

“Decentering” reflects psychological flexibility in people with chronic pain and correlates with their quality of functioning.

Abstract: People with chronic pain may benefit from the capacity to contact their thoughts and feelings from a perspective as a "separate observer," to see them as transient, and to experience them as cognitively "defused."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 13 publications
4
46
0
2
Order By: Relevance
“…The 12-item decentering scale from the Experiences Questionnaire (EQ; Fresco et al, 2007; McCracken et al, 2013b) was used here. It reflects the ability to observe one's thoughts and feelings as temporary, objective events in the mind and not necessarily true reflections of oneself or one's circumstances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12-item decentering scale from the Experiences Questionnaire (EQ; Fresco et al, 2007; McCracken et al, 2013b) was used here. It reflects the ability to observe one's thoughts and feelings as temporary, objective events in the mind and not necessarily true reflections of oneself or one's circumstances.…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores suggest greater decentering. The EQ has been validated among people with chronic pain (McCracken et al, 2013b). The decentering scale showed good internal consistency in the current sample (Cronbach's α = 0.85).…”
Section: Methodsmentioning
confidence: 99%
“…Some of its six constituent processes of PF, however, are gaining prominence, especially acceptance, 4,10,11,18,26,56,58,69,84,87,97 and values-based action. 55,56,59,67,84 Even the least well recognized processes of PF now have some empirical support, including present-focused awareness, 51 cognitive defusion and self-as-observer, 53 and committed action. 49 A meta-analysis of the processes of PF, including 66 experimental laboratory studies, many employing transient pain exposure, concluded that there is support for significant positive effects on outcomes for acceptance, values-based-action, cognitive defusion, present-focused awareness, and committed action.…”
Section: Current Psychological Models Of Chronic Pain Under a Microscopementioning
confidence: 99%
“…Kabat-Zinn’s world-renowned Mindfulness-Based Stress Reduction (MBSR) Clinic, founded in 1979, provides training to participants so that they may develop the capacity to observe their own thoughts and feelings from a detached perspective (McCracken et al, 2013), and thus see themselves as if they were to “video-tape someone else” (Gallagher, 2000), and in turn to view their pain, together with their pain-elicited emotions and judgments, as transient passing events rather than as reflections of the self or reality (McCracken et al, 2013). MBSR’s effect on chronic pain patients has been well established as an outpatient program in behavioral medicine (Kabat-Zinn, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness-based stress reduction training is in fact a means to cognitively “re-construct” participants’ perception of pain, through developing their capacity to observe their own thoughts and feelings from a detached perspective (McCracken et al, 2013). The purpose of such a perspective shift is to place oneself in another’s position, which is empathy, defined as the capacity to understand or feel what another person is experiencing from within the other being’s frame of reference (Bellet and Maloney, 1991).…”
Section: Introductionmentioning
confidence: 99%